Designing an online resource for collaborative GCSE Mathematics revision - Bowman, Katherine (2016)
Education has embraced a constructivist way of learning within British secondary classrooms, with Ofsted naming student centred learning as an element of effective teaching and the 2015 National Curriculum for Mathematics citing discussion as a means to remedy misconceptions. Never-the-less, the bulk of revision materials which can be found online follow a behaviourist learning style, with teachers telling students how to solve problems and posing a multitude of practice questions. A review of literature was conducted to find out how the constructivist approach to learning could be embraced in the online environment. This dissertation explains how the theory was used to design a revision resource for a group of students who were studying for their Mathematics GCSE. It further details the support which was given to students when implementing the revision resource and how data was collected through observations, questionnaires and group interviews. Analysis of the initial findings revealed the students were not motivated to contribute to the revision resource. The adaptations which were made to the revision resource to foster motivation are justified before analysing the findings from the adapted design. The dissertation concludes that the most important feature of an online learning environment is motivation, as without motivation there is no learning. It urges further research into suggestions on how to foster that motivation in students who lack confidence in their ability, highlighting the differences between these students and the Higher Education students who are the main subject of current research (Barbour, 2012).